STUDY OF ANTI-INFLAMMATORY ACTIVITY OF NANOEMULSION- BASED GEL OF CURCUMIN IN ACUTE AND CHRONIC INFLAMMATORY MODEL - Permatasari, Dahlia
Background and Objective: Curcumin, a natural polyphenolic phytochemical, has shown to be effective as an anti-inflammatory agent but has the major limitation such as poor stability and low bioavaibility. In previous research, curcumin nanoemulsion was established using cremophor RH40 as a surfactant and resulted good characteristic of nanoemulsion. However, due to the adverse effect risk upon using long-term cremophor RH40 as a surfactant, same formula was developed but using Tween 20 instead of cremophor RH40. The purpose of this study was to formulate and characterize curcumin nanoemulsion using Tween 20 as a surfactant for transdermal application and evaluate its efficacy in acute and chronic inflammatory model. Method: Curcumin nanoemulsions were prepared by self nano emulsification method using GMO, Tween 20 and PEG 400 in ratio 1:8:1 as an oil phase with optimization the amount of curcumin to be entrapped. Evaluation of curcumin nanoemulsion was carried out including to particle size analysis, polydispersity index, morphology, loading efficiency and thermal property. Stability of nanoemulsion were performed at room temperature, 70°C and freeze thaw test cycle. Further, curcumin nanoemulsion were incorporated into gel using menthol as a penetration enhancer. The gel was then evaluated including in vitro diffusion test and in vivo antiinflammatory activity and irritation test. Anti-inflammatory activity was evaluated in acute inflammatory model using carrageenan and chronic inflammatory model using complete Freund’s adjuvant (CFA) as an inducer. Results: Self nanoemulsion with loading capacity of 10 mg curcumin per 1 g of oil phase was stable under room temperature for 14 d and over 6 cycles of freeze thaw test. The diffusion test showed that permeation of curcumin from nanoemulsion gel containing 1% menthol was 10.18 fold higher compared to conventional curcumin gel. Gel of curcumin nanoemulsion containing 1% mentol as a penetration enhancer inhibits the formation of inflammation siginificantly (p<0.005) and has similar anti-inflammatory activity with 1% diclofenac sodium gel in acute model. In chronic model, gel of curcumin nanoemulsion containing 1% menthol inhibits the formation of inflammation better than other gel formula and cause no irritation to the skin Conclusion : Tween 20 seems to be promising surfactant for long-term use of nanoemulsion for topical therapeutic purpose. Gel of curcumin nanoemulsion with the addition of 1% mentol increase the curcumin permeation and has an anti-inflammatory effect in acute inflammation model without causing irritation to the skin.